2008
DOI: 10.1177/0887403407309038
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence Statutes and Rates of Intimate Partner and Family Homicide

Abstract: This study explores whether states adopting specific domestic violence laws have significantly lower rates of intimate partner and family homicide, as well as a lower average of the two homicide rates. Point biserial correlation and multiple regression were used to analyze homicide rates, as measures of domestic violence, across seven statutory categories of state domestic violence laws for 47 continental states in the United States. With two exceptions, data show that state laws on domestic violence were not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Zeoli and Webster (2010) also found that rates of intimate partner homicide were reduced in states where firearms access was restricted for those with Domestic Violence Restraining Orders (DVROs), as well as in states that allowed arrests without warrants for DVRO violations. However, Bridges, Tatum, and Kunselman (2008) found no significant correlations between intimate partner homicide and states that prohibited firearm possession during a restraining order. However, the authors note two outlier states that did have inverse correlations between firearm restriction laws and intimate partner homicides (Bridges et al, 2008).…”
Section: Current Researchmentioning
confidence: 78%
See 2 more Smart Citations
“…Zeoli and Webster (2010) also found that rates of intimate partner homicide were reduced in states where firearms access was restricted for those with Domestic Violence Restraining Orders (DVROs), as well as in states that allowed arrests without warrants for DVRO violations. However, Bridges, Tatum, and Kunselman (2008) found no significant correlations between intimate partner homicide and states that prohibited firearm possession during a restraining order. However, the authors note two outlier states that did have inverse correlations between firearm restriction laws and intimate partner homicides (Bridges et al, 2008).…”
Section: Current Researchmentioning
confidence: 78%
“…However, Bridges, Tatum, and Kunselman (2008) found no significant correlations between intimate partner homicide and states that prohibited firearm possession during a restraining order. However, the authors note two outlier states that did have inverse correlations between firearm restriction laws and intimate partner homicides (Bridges et al, 2008). Although there is some supporting evidence that gun restrictions can reduce the rate of intimate partner homicides, this research remains open to more than one interpretation.…”
Section: Current Researchmentioning
confidence: 78%
See 1 more Smart Citation
“…In the interests of brevity, a detailed review is not presented in this article; however, for additional information, the reader is referred to Frattaroli and Vernick (2006), Vigdor and Mercy (2006), and Webster and Wintemute (2015). Briefly, though, relevant legislative approaches fall into two dominant groups: laws to limit firearms access by persons who commit acts of domestic and family violence, using mechanisms such as linking apprehended violence or restraining orders with firearm prohibition orders and mandatory surrender of firearms (e.g., Bridges, Tatum, & Kunselman, 2008; Dugan, 2003; Raissian, 2016; Vigdor & Mercy, 2006; Vittes et al, 2013; Zeoli & Webster, 2010), and laws to limit firearm access by persons with general “disqualifying” offenses, such as violent misdemeanors (including but not limited to domestic and family violence), using measures such as background checks and purchase prohibition orders (e.g., Wright & Wintemute, 2010; Wright, Wintemute, & Rivara, 1999).…”
Section: Current Knowledge About Potentially Effective Legislative Inmentioning
confidence: 99%
“…This research generally suggests that such homicides are less prevalent in the context of laws preventing people with histories of intimate partner violence from owning guns. For example, intimate partner homicide rates are significantly lower in states with laws that restrict access or remove firearms from homes in which domestic violence occurs, with stronger effects in states with the strictest laws and enforcement, in states with the most severe penalties for violations, when restrictions are tied to the presence of a domestic violence-related restraining order, and when laws target point of purchase behaviors (Bridges, Tatum, and Kunselman 2008; Vigdor and Mercy 2006; Vigdor and Mercy 2003; Zeoli and Webster 2010). Of note, however, is that these state-level analyses only found significant inverse associations with intimate partner homicides between laws restricting firearms from those under domestic violence restraining orders, but not laws that restricted firearms from convicted domestic violence misdemeanants.…”
Section: Introductionmentioning
confidence: 99%